Cancer patients' satisfaction on nursing care - Luciana Da Conceição Silva; Irena Penha Duprat; Marinho Da Silva Correia; Havany Thayany Pereira Ramalho; Josemir De Almeida Lima (Universidade Federal do Ceará, 2015)
Objective: to analyze the satisfaction of cancer patients on nursing care. Methods: descriptive quantitative research with 190 patients receiving outpatient chemotherapy in the High Complexity Centre in Oncology, through a questionnaire. Results: 185 respondents (97.4%; 95.0% CI 94.7 to 99.9) said they were always satisfied with the care provided, however, less than a third assessed that charisma (34.2%; 95.0% CI 27.4 to 39.5), respect for their decisions (31.6%; 95.0% CI 24.7 to 37.4) and clear communication (26.3%, CI 20.0 to 31.1) were decisive factors for their satisfaction. Conclusion: the study revealed an excellent level of patient satisfaction on nursing care, although some factors considered by users as decisive for the identification of this feeling have not been significantly identified. This justifies the need for critical reflection, in the professional's view, that fosters the implementation of changes and to better meet the expectations and needs of the patient.